DEVELOPING AN INTEGRATED ENGLISH EDULITERATURE SYLLABUS FOR MTS PESANTREN AL-AMIN MOJOKERTO - Suharyono, Suharyono; Islam, Aang Fatihul (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2024)
Pondok Pesantren Al-Amin Mojokerto is developing an effective English Language Teaching. Language program of Madrasah, under 2013 Curriculum, and pesantren, which has no guideline, cannot go together to help students mastering English. The unavailability of syllabus as guideline becomes a major problem. By conducting Research and Development (R&D) the researcher developed an integrated English syllabus for all English teaching in madrasah and pesantren. The syllabus was integrated syllabus for MTs level. It integrated madrasah language teaching, pesantren language teaching covering morning program, conversation and khitobah. Government demand (2013 curriculum), institution expecation and students’ needs are accomodated with this syllabus.